A vivência do trabalho em professoras de escolas privadas durante a pandemia do COVID-19 - Nüssle, Flora Santos (2021)
In 2020 the new coronavirus brought about a completely new dynamic for professionals in all areas, such as the private school teacher. This occupation has a mostly female workforce, occupying up to 82% of the positions in elementary education. Thus, the objective of this dissertation is to analyze how female private school teachers experience their work during the covid-19 pandemic. The research is theoretically based on Vygotsky's Cultural-Historical perspective and counts on the participation of 12 female teachers who teach elementary school in private schools in the city of Natal/RN. The methodology chosen was the application of an in-depth interview conducted online through the Google Meet platform. This was divided into four axes, namely: socioeconomic data, work life history, work context, and dramas at work. The data collected were categorized with the help of the QDA Miner platform and to analyze them, the three stages of the Nuclei of Meaning were performed. In the first stage, from the floating reading of the interviews 58 pre-indicators were listed, which were later agglutinated into 19 indicators and, finally, these indicators formed five nuclei of meaning. The cores are: the meanings produced by women about the work as a teacher; the difficulties of the daily life of a teacher; the consequences of the pandemic arrival; the aggravations generated by the pandemic; and the challenges faced. In view of these findings, we understand that the pandemic acted as a catalyst for the difficulties of work that already existed in the daily lives of private school teachers. And that the different ways they experience these difficulties, as well as face them, is a consequence of a social and historical system implied by neoliberal capitalism, by the processes of precarization, outsourcing, as well as by the formation of the school and the sexual division of labor.